2016
DOI: 10.1136/gutjnl-2016-311526
|View full text |Cite
|
Sign up to set email alerts
|

Plasma DNA methylation: a potential biomarker for stratification of liver fibrosis in non-alcoholic fatty liver disease

Abstract: Objective Liver biopsy is currently the most reliable way of evaluating liver fibrosis in patients with Non-Alcoholic Fatty Liver Disease (NAFLD). Its inherent risks limit its widespread use. Differential liver DNA methylation of PPARγ gene promoter has recently been shown to stratify patients in terms of fibrosis severity but requires access to liver tissue. The aim of this study was to assess whether DNA methylation of circulating DNA could be detected in human plasma and potentially used to stratify liver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(151 citation statements)
references
References 35 publications
(46 reference statements)
0
147
1
3
Order By: Relevance
“…Using liver biopsy tissue from NAFLD patients, Sookoian et al identified methylation of promoter sites on PPARγ coactivator 1α (PPARGC1A) with markers of insulin resistance such as HOMA-IR and serum insulin (19). Other investigators have demonstrated that specific methylation sites on promoters of genes are linked to more severe liver fibrosis (17,18). Although these reports establish a potential relationship between fibrosis and specific epigenetic modifications, targeted individual CpG sites may not accurately reflect the complex interaction between causal and compensatory measures in chronic diseases such as NASH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using liver biopsy tissue from NAFLD patients, Sookoian et al identified methylation of promoter sites on PPARγ coactivator 1α (PPARGC1A) with markers of insulin resistance such as HOMA-IR and serum insulin (19). Other investigators have demonstrated that specific methylation sites on promoters of genes are linked to more severe liver fibrosis (17,18). Although these reports establish a potential relationship between fibrosis and specific epigenetic modifications, targeted individual CpG sites may not accurately reflect the complex interaction between causal and compensatory measures in chronic diseases such as NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of DNAm in NAFLD have examined gene-specific epigenetic modifications that may be involved in disease pathogenesis by targeting genes known to regulate fibrogenesis or metabolic function (16)(17)(18)(19)(20). For instance, Hardy et al examined two specific CpG loci on the PPARγ promoter in circulating DNA and found differences in methylation between NAFLD patients with severe fibrosis and those with mild fibrosis (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remodelling of DNA methylation at key fibrosis modifier genes underpinned protection against carbon tetrachloride (CCl 4 ) induced liver fibrosis in male offspring of male mice that were themselves subjected to CCl 4 mediated liver injury 104 . Remarkably, DNA methyl ation remodelling occurred in the same genes in patients with NASH with mild fibrosis and intriguing data sug gests that epigenetic signatures present on circulating cell free DNA could be a potential biomarker of this effect and, therefore, disease severity 104,105 .…”
Section: Risk Factors: Nature or Nurture?mentioning
confidence: 98%
“…Finally, exocrine pancreas-derived DNA was identified in patients with pancreatitis. Other researchers suggest ccfDNA methylation as a potential biomarker for stratification of liver fibrosis in non-alcoholic fatty liver disease [24]. Cardiac diseases might be accompanied by elevated levels of ccfDNA and is found in patients with acute coronary syndrome [25].…”
Section: Other Diseases Beyond Cancermentioning
confidence: 99%